The test–retest reliability of the Military Physical Loading Questionnaire (MPLQ). Issue 4 (30th March 2020) - Coppack, Russell J; Bilzon, J L; Wills, A K; Papadopoulou, T; Cassidy, R P; Nicol, A M; Bennett, A N
Abstract : Introduction: Despite the high prevalence of musculoskeletal injuries, there is a shortage of data quantifying the risk factors attributable to cumulative occupational demands among UK Military personnel. We developed a new comprehensive questionnaire that examines occupational and operational physical loading during military service. The aim of this study was to examine the test–retest reliability of the Military Physical Loading Questionnaire (MPLQ). Methods: Intraclass correlation coefficients (ICC) were used to evaluate the test–retest reliability (4-week interval) of the MPLQ on 18 occupational and 18 operational items in 50 male (mean age: 36 years; SD ±7.9) UK military personnel. A stratified analysis based on duration of Service (0–10 years, 11–20 years and ≥21 years) was conducted to assess whether stability of task items was dependent on participant length of recall. Internal consistency was assessed by Cronbach's alpha (α) coefficients. Results: Reliability of individual operational items ranged from fair to almost perfect agreement (ICC range: 0.37–0.89; α range: 0.53–0.94) with most items demonstrating moderate to substantial reliability. Overall scores related to occupational items showed substantial to almost perfect agreement between administrations (ICC range: 0.73–0.94; α range: 0.84–0.96). Stratifying by duration of Service showed similar within group reliability to the entire sample and no pattern of decreasing or increasing reliability with length of recall period was observed. Conclusions: It is essential that data used in planning UK military policy and health services are as accurate as possible. This study provides preliminary support for the MPLQ as a reliable self-report instrument for assessing the cumulative lifelong effects of occupational loading in UK military personnel. Further validation studies using larger and more demographically diverse military populations will support its interpretation in future epidemiological research.